Biopolymers reuse, recycling, and disposal - Niaounakis, Michael (Elsevier Science, 2013)
Biopolymers Reuse, Recycling and Disposal is the first book covering all aspects of biopolymer waste management and post-usage scenarios, embracing existing technologies, applications, and the behavior of biopolymers in various waste streams. The book investigates the benefits and weaknesses, social, economic and environmental impacts, and regulatory aspects of each technology. It covers different types of recycling and degradation, as well as life cycle analysis, all supported by case studies, literature references, and detailed information about global patents.
Keywords: biopolymery; biopolymers; elektronické knihy; electronic books